Medical Students Knowledge and Attitude Towards Direct-To-Consumer Genetic Tests (Epidemiology, Biostatistics, and Public Health, 2022)
Aims: This study reports on the attitudes of 179 Italian Medical Students to direct-to-consumer genetic test and to participation in research practices.Methods: Data were collected using a self-completion online questionnaire sent to 380 medical students at the faculty of Medicine of the Università Cattolica del Sacro Cuore in Rome, Italy. Questions pertained issues related to awareness and attitudes towards genetic testing, reactions to hypothetical results, and views about contributing to scientific research.Results: The response rate was 47.1%. Less than 50% of students were aware of DTC genetic test. Seventy-four percent of the sample were interested in undergoing DTC genetic test, and the main reason was being aware on genetic predisposition to diseases. Among those who were not willing to undergo a genetic test, the main reason was the lack of confidence in the results. In the hypothetical situations of an increased disease risk after undergoing DTC genetic testing, respondents would take actions to reduce that risk, while in the opposite scenario they would feel unaffected because of the probabilistic nature of the test.Conclusions: We reported a good level of awareness about DTC genetic test and a high interest in undergoing DTC genetic test in our sample. Nevertheless, opinions and reactions are strongly dependent by the hypothetical good or bad result that the test could provide and by the context whereby a genetic test could be performed. Respondents seem to be exposed to the risk of psychological harms, and a strong regulation regarding their use is required.